Reading Class Struggle and Promoting Class Consciousness through Bob Marley's Protest Songs - Nangwaya, Ajamu; Onuora, Adwoa Ntozake (Caribbean quarterly, 2018)
This paper will argue that given the vagueness of the metaphors and the absence of analytical and prescriptive details on the subject of freedom and exploitation in many of Bob Marley’s songs, progressive class-conscious educators, radio disc jockeys, organisers and intellectuals ought to illuminate the class solidarity, class interest, class consciousness and class struggle themes that are embedded in the work of this cultural icon. The goal of this approach to reading Bob’s protest songs is to raise the awareness of the "downpressed" and their allies about the inherently oppressive character of capitalism and the distinct class interests of the labouring classes.